2018
DOI: 10.15421/021803
|View full text |Cite
|
Sign up to set email alerts
|

Content of chemical elements in the liver of cattle with fasciolosis and dicrocoeliosis

Abstract: The concentration of chemical ements (Pb, Cd, Cu, As, Zn, Hg, Fe, Co, Mn) in the liver of healthy cattle and those affected by Fasciola hepatica and Dicrocoelium lanceatum in Poltava region (central part of Ukraine) was determined. The research was carried out by the method of atomic and absorption spectrometry carried out at the Regional State Laboratory of Veterinary Medicine in Poltava region. The liver samples (n = 30) from healthy cattle black-and-white breed and those affected by F. hepatica and D. lance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Studies on fish have reported that the older the age and the bigger the body size, the higher the contamination (Farkas et al 2003;Govind and Madhuri 2014). Furthermore, many factors influence the level of contamination, including geographic and fish species (El-Moselhy et al 2014), physiological fish (Govind and Madhuri 2014), tissue types (Garcia et al 2011;Muselin et al 2010;Okareh et al 2015), and certain infections (Kruchynenko et al 2018). In contrast to the results of experiments using rats, where it was reported that the young were more exposed to lead than the older rats, but the younger animals have higher metabolic rate causing the heavy metals tobe rapidly accumulated (Blagojević et al 2012), and this caused persistent immunotoxicity (Miller et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on fish have reported that the older the age and the bigger the body size, the higher the contamination (Farkas et al 2003;Govind and Madhuri 2014). Furthermore, many factors influence the level of contamination, including geographic and fish species (El-Moselhy et al 2014), physiological fish (Govind and Madhuri 2014), tissue types (Garcia et al 2011;Muselin et al 2010;Okareh et al 2015), and certain infections (Kruchynenko et al 2018). In contrast to the results of experiments using rats, where it was reported that the young were more exposed to lead than the older rats, but the younger animals have higher metabolic rate causing the heavy metals tobe rapidly accumulated (Blagojević et al 2012), and this caused persistent immunotoxicity (Miller et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Відповідно до даних науковців, що проводили паразитологічні дослідження у господарствах на території центрального регіону України встановлено, що у корів віком від 3-х до 8-ми років зареєстровано найвищі показники екстенсивності інвазії (24,1 %) за шлунково-кишкових стронгілід із родів: Haemonchus, Bunostomum і Oesophagostomum [8]. Ці дані збігаються з нашими дослідженнями, оскільки у великої рогатої худоби, овець і кіз представники стронгілід шлунково-кишкового тракту також є найбільш чисельною групою паразитів.…”
Section: 5%unclassified